Shifts in soil phosphorus fractions during seasonal transitions in a riparian floodplain wetland - Coppolino, Jacob; Munford, Kimber E.; Macrae, Merrin; Glasauer, Susan (Frontiers in Environmental Science, 2022)
Losses of phosphorus from soil to surface waters in agricultural areas have been linked to substantial declines in water quality. Riparian wetlands can potentially intercept phosphorus mobilized from upland soils before it reaches connecting waterways, but the capacity of wetlands to buffer against downstream losses of P is poorly understood, especially in northern temperate zones. In these regions, the spring freshet releases large volumes of water from snowmelt and soil pore water during the time when microbial productivity, which transfers available P into biomass, is low. In addition, losses of P in runoff may be exacerbated by freeze-thaw cycling (FTC) in soil during late winter and early spring through the physical degradation of organic matter. We investigated P dynamics from late fall through spring thaw and into summer to assess P transfers between inorganic, organic and microbial biomass pools, as functions of season and distance from a river. The site is located on the Grand River in southern Ontario, which discharges to Lake Erie, and consists of riparian wetland and wooded areas. Reactive P (Olsen P) and microbial biomass P (PMBIO) increased with distance from the river and varied more over time in the wetland soil compared to the adjacent wooded area, reflecting higher variability in vegetation, topography and hydrology. The positive correlation between microbial biomass P and microbes linked to ammonification supports the release of N and P through mineralization pathways as spring progresses, with microbial biomass decreasing in June as plant growth increases. There was evidence for leaching of Fe and Al, and lower concentrations of total P, in the transect proximate to the river. Seasonal flooding during spring thaw contributed to a pulse of dissolved reactive P, but temperature monitoring showed that the wetland soil did not experience freeze-thaw cycling. Investigation of FTC using wetland soil in mesocosms indicated that multiple FTC (>3) were necessary to increase the pool of reactive soil P, with the highest amount of soil reactive P observed after 6 FTC, when dissolved reactive P also tended to increase.